Opportunities and Challenges of Pentahelix Collaboration for Poverty Alleviation in Indonesia: A Systematic Literature Review - Tadung, Edy (KnE Social Sciences, 2023)
Within the context of poverty reduction, there is a clear tendency for groups or organizations involved in these efforts to continue existing practices or approaches without producing the necessary changes or innovations. We found that the poverty reduction gap occurs when programs or projects that have been carried out together repeatedly fail to deliver the expected results in reducing poverty significantly. Despite the awareness of the need for change through collaboration, they still seem to adhere to old approaches that are familiar, routine, or ineffective. Although the pentahelix model partnership is not an easy solution to difficult societal issues, the public views it as an opportunity and challenge that occasionally frustrates the parties involved and raises public expectations. For practitioners, researchers, and decision-makers, this study identifies trends, possibilities, and problems in the development of a larger pentahelix model network of collaborative knowledge generation. Keywords: pentahelix collaboration, bibliometric review, poverty alleviation